Auditory Verbal Hallucinations in Schizophrenia From a Levels of Explanation Perspective. (24th October 2017) - Hugdahl, Kenneth; Sommer, Iris E
Abstract: In the present article, we present a "Levels of Explanation" (LoE) approach to auditory verbal hallucinations (AVHs) in schizophrenia. Mental phenomena can be understood at different levels of explanation, including cultural, clinical, cognitive, brain imaging, cellular, and molecular levels. Current research on AVHs is characterized by accumulation of data at all levels, but with little or no interaction of findings between levels. A second advantage with a Levels of Explanation approach is that it fosters interdisciplinarity and collaboration across traditional borders, facilitating a real breakthrough in future research. We exemplify a Levels of Explanation approach with data from 3 levels where findings at 1 level provide predictions for another level. More specifically, we show how functional neuroimaging data at the brain level correspond with behavioral data at the cognitive level, and how data at these 2 levels correspond with recent findings of changes in neurotransmitter function at the cellular level. We further discuss implications for new therapeutic interventions, and the article is ended by suggestion how future research could incorporate genetic influences on AVHs at the molecular level of explanation by providing examples for animal work.